Believers and Their Disbelief - King, Thomas M. (Zygon, 2007)
Abstract. Several recent Roman Catholics who were known for their devotion have left accounts of their troubled faith. I consider three of these: St. Therese of Lisieux, Mother Teresa of Calcutta, and Pierre Teilhard de Chardin. Then I tell of the troubled atheism of Jean-Paul Sartre. Finally, I use texts of Sartre and Teilhard to understand the unsettled nature of belief.